Assessing the synergistic effects of inorganic, organic, and biofertilizers on rhizosphere properties and yield of maize - Lolita Endang Susilowati; Sukartono Sukartono; Muhammad Firman Akbar; Bambang Hari Kusumo; Ahmad Suriadi; Amin Setyo Leksono; Fahrudin Fahrudin (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
A single and long-term use of inorganic fertilizers harms soil quality. Therefore, it is highly recommended that inorganic fertilizers be combined with other fertilizers. This study explores the synergistic effect of inorganic, organic, and biofertilizers on maize rhizosphere properties and production. Biochar (BC) and compost (OF) were applied as organic sources, a consortium of phosphate solubilizing bacteria (PSB) was applied as phosphate biofertilizers, while urea and NPK-PONSKA fertilizers (IF) were used as inorganic fertilizers. A greenhouse experiment was designed as a completely randomized arrangement involving six treatments in triplicate, namely control (only IF), a combination of IF+BC, IF+PSB, IF+BC+PSB, IF+PSB+OF, and IF+BC+OF+PSB. The best changes in soil microbial and chemical properties, maize root dry weight, and production were observed in the IF+BC+OF+PSB combination, followed by IF+OF+PSB, IF+BC+PSB and (IF+BC; IF+PSB) and control treatment, respectively. A fertilizer combination involving the addition of BC (IF+BC, IF+BC+PSB, IF+BC+OF +PSB) significantly increased soil organic C content and soil pH compared to without biochar (IF+PSB and IF+OF+PSB). A higher root dry weight also results in higher maize production. Maize production Increased in the 4, 3, and 2 combinations compared to production in the control by 43.11%, 31.32-36.55%, and 18.57%-21.34%, respectively. In conclusion, the synergy of biochar, compost, and PSB, when integrated with fertilizer, can improve soil quality and the sustainability of maize production. This study will be useful in developing sustainable nutrient management programs to increase crop productivity with high efficiency in using inorganic fertilizers.Barbarslot adalah salah satu situs resmi slot deposit 5000, 5rb dan depo 5k terbaru dengan beragam permainan terbaik tahun 2025.